Optimizing Village Assets and Stakeholder Engagement for Income Growth - Satriyo, Muhammad Iqbal; Agustina, Isna Fitri (Universitas Muhammadiyah Sidoarjo, 2024)
General background, many Indonesian villages have economic potential that requires strategic development. Specific background, Bluru Kidul struggles with asset utilization and income generation. Knowledge gap, strategies for improving Village Original Income (PADesa) in similar contexts are underexplored. Aims, this study analyzes the village government’s strategies to increase income. Results, qualitative research reveals that while internal stakeholders like BUMDes and PKK are engaged, income targets remain unmet due to inconsistent training and limited actions. Novelty, the study identifies the lack of consistent training as a key issue. Implications, improving training and resource mobilization can enhance income generation and provide a model for other villages. Highlights: Village income is hindered by poor asset management and undeveloped potential. Stakeholders like BUMDes and PKK are involved but not fully optimized. Inconsistent training limits income growth despite efforts. Keywords: Village Government, Income Strategy, Asset Management, Village Original Income, Training